Las fotos escolares como “analizadores” en la investigación educativa. - Fischman, Gustavo (2008)
This article proposes the use of school photographs as research “analyzers” of educational institutions. After a brief discussion about the limitations of approaches that consider photographs as transparent and always clearly evident containers of meaning and evidence, this article introduces the notion of school photographs as research “analyzers” and discusses its relationship with the photo-elicitation methods and qualitative research. The conceptual discussion is grounded in the analysis of two school-photographs. To conclude this article elaborates on key parameters needed when using this approach.